The plight of indigenous peoples within the context of conflict mediation, peace talks and human rights in Mindanao, the Philippines - Candelaria, Sedfrey M (Archīum Ateneo, 2018)
Republic Act 8371 or the Indigenous Peoples’ Rights Act of 1997 (IPRA) was passed by the Philippine Congress in order to address the concerns of the indigenous communities which had received marginal attention through the past decades. Indigenous communities have also been displaced from their lands due to armed conflicts between government soldiers and secessionist groups, particularly the Moro rebels and the communist-led New Peoples’ Army. The Philippines has been privy to peace initiatives with these two groups for some time now. Political circumstances, however, and legal impediments have periodically stalled the peace processes. It is the author’s intention to focus on the predicament of indigenous communities as they seek a strategic role in shaping the content of peace agreements being negotiated by the Philippine government with the rebel groups. How have the indigenous communities made an impression on the two peace processes through the years? And, have the indigenous peoples’ rights been sufficiently protected in the context of the peace agreements? The author will draw from his own insights on the peace processes and agreements which have been negotiated and even tested before the Supreme Court of the Philippines.